Dampak Pemerintah Desa dalam Meningkatkan Pemberdayaan Ekonomi Masyarakat Nelayan Desa Leme-Leme Bungin Kab. Banggai Kepulauan - Muh. Rifaldi Latarang; Sriwaningsih S Nahe; Farhan A. Bidullah; Mutmainah Mutmainah; Abdul Jalil; Fatimawali Fatimawali (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This stu dy aims to analyze the role and contribution of the Village Government of Leme-Leme Bungin in enhancing the economic empowerment of the fishing community. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that assistance programs, such as the provision of boats and engines, have had a positive impact on improving the productivity and economic welfare of fishermen. However, the implementation of these programs still faces several challenges, including equipment mismatch, extreme weather, limited technical training, and restricted market access. Additionally, the suboptimal performance of the Village-Owned Enterprises (BUMDes) also affects the effectiveness of empowerment efforts. Strong collaboration between the village government, the community, and supporting institutions is required to achieve sustainable and inclusive empowerment.